Exploring organizational adoption of cloud computing in Singapore - Margaret Tan; Trisha T. C. Lin (International Telecommunications Society (ITS), 2012)
Cloud computing constructs a new environment to enable resource sharing in terms of scalable infrastructures, middleware and application platforms and value-added business models. It offers the advantages of flexibility and scalability to business operations, reduction in total costs of computing, thus achieving higher return on investment. However, the technology raises pertinent concerns on security risk, data privacy, data segregation in the cloud and long-term viability of providers. Owing to the potential for cloud computing, more research is needed to understand the factors influencing its adoption. This study therefore aims to examine to what extent Singapore companies adopt cloud computing, and how organizational factors, perceived characteristics of cloud computing, and environmental factors affect the adoption. An online survey was conducted of enterprises from a wide range of industries. This paper will further contribute to the knowledge on the factors of cloud computing adoption, thus we hope to mystify the differences between the hype espoused by vendors versus what is really perceived by the organizations.
Keywords: 330; cloud computing adoption; organizational factors; perceive characteristics of innovation; environmental factor.